Battery-type and binder-free MgCo2O4-NWs@NF electrode materials for the assembly of advanced hybrid supercapacitors. (26th April 2022) - Chen, Huiyu; Liu, Yafei; Wu, Runze; Liu, Xiaohong; Liu, Yan; Xu, Chunju
Abstract: In this study, the hetero-structure of MgCo2 O4 nanowires (MCO-NWs) and microcubes (MCO-MCs) on the skeleton of nickel foam (NF) was realized through a simple hydrothermal method and subsequent annealing treatment, and then served as a binder-free cathode for assembly of high-performance hybrid supercapacitor (HSC). Such synthetic methodology avoided the traditional usage of conductive and binder reagents for the electrode fabrication. The electrochemical tests indicated its battery-type characteristics, and the MCO-NWs@NF exhibited a huge specific capacity ( C s ) of 389.0 C g −1 as well as 86.2% capacity retention when the current density boosted from 1 to 10 A g −1 . The assembled HSC with activated carbon (AC) as anode further demonstrated the advantages of this electrode material. After 5000 cycles at 6 A g −1, the MCO-NWs@NF//AC HSC showed good long-term cycling stability without any decay in capacitance, and could deliver an energy density ( E d ) of 37.9 W h kg −1 at the power density ( P d ) of 958.1 W kg −1, higher than the 30.4 W h kg −1 of MCs-based HSC. These impressive results regarding electrochemical performance suggest that MCO-NWs@NF may be a promising candidate to serve as a battery-type material in electrochemical energy storage applications such as HSCs, batteries, and so on. Graphical abstract: MgCo2O4 nanowires (NWs) were directly grown on nickel foam (NF) via an initial hydrothermal route with an extra annealing treatment of precursor. The binder-free MgCo2O4-NWs@NF electrode exhibited battery-type electrochemical response with a huge capacity of 389.0 C g −1 at 1 A g−1 in 2 M of KOH electrolyte. The assembled MgCo2O4-NWs@NF//AC hybrid supercapacitor delivered a high energy density of 37.9 W h kg−1 at a power density of 958.1 W kg−1 . Image 1 Highlights: MgCo2 O4 nanowires on Ni foam were hydrothermally prepared. A highly specific capacity of 389.0 C g −1 at 1 A g −1 was obtained. 86.2% rate capability was reached with current density increasing from 1 to 10 A g −1 . The HSC device delivered an energy density of 37.9 W h kg −1 at 958.1 W kg −1 .